Islamic Studies of Indonesian Malay Community: A Perspective from Psychology of Religion - Muh. Mawangir, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Malay culture is a transformation from the assimilation process into Malay culture and civilization in Archipelagos. Islam has formed a determinant aspect on the process of political, cultural, psychological and social systems in society. The interaction between Malay Archipelagos communities both individually and in social groups is based on the teachings of the Islamic religion, namely belief in the one and only God. The life style of the Indonesian Malay community is known as a symbol of Malay culture which position can be developed, recognized, appreciated and respected by tribes or ethnic groups in other Archipelagos communities. A noble and cultural-loving personality is characteristic of Indonesian Malay community. In the perspective of psychology of Religion, the Indonesian Malay community has basically instilled an order of Islamic religious values in aspects of their life. Functioned in fostering moral and mental religion of the Malay community in the everyday life’s attitude.